Evaluating the Effectiveness of Innovative Learning Approaches in Teaching Biology to Secondary School Students: A Comparative Study of Traditional and Interactive Pedagogical Methods - Bhoi, Chandrasekhar (Journal of Education Method and Learning Strategy, 2024)
As the landscape of education continues to evolve, it is crucial for educators to stay abreast of the innovative strategies and approaches in order to effectively prepare students for the complexities of the 21st century. This comprehensive review underscores the significance of embracing diverse and dynamic teaching methodologies to cultivate a deep and enduring passion for biology among school students. In order to address diverse learning styles and abilities, personalized learning strategies, differentiated instruction, and the incorporation of multimedia resources have been increasingly utilized to cater to individual student needs and promote inclusive in biology education. Furthermore, the implementation of formative assessments and feedback mechanisms has allowed for ongoing evaluation and adaptation of teaching methods to optimize student learning outcomes. Additionally, the integration of interdisciplinary studies, such as combining biology with technology, ethics, and environmental science, has provided students with a broader and more holistic perspective on biology and its relevance in the real world. By embracing innovative teaching strategy  and staying attuned to the evolving needs of students, educators can cultivate a vibrant and engaging learning environment that empowers students to become informed and enthusiastic participants in the ever-expanding field of biology.